Miners working the No. 7 bench claim, Anvil Creek, Alaska, approximately 1900. - Hegg, Eric A., 1867-1948 (1900)
Shows men and women standing in front of mine shaft with tramcar. Caption on image: "Bench No. 7 Anvil" Original image in Hegg Album 28, page 8. Nome Gold Rush.